If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2p + 4(1 + -1p) = 4 + -1(2)(1 + -1p) 2p + (1 * 4 + -1p * 4) = 4 + -1(2)(1 + -1p) 2p + (4 + -4p) = 4 + -1(2)(1 + -1p) Reorder the terms: 4 + 2p + -4p = 4 + -1(2)(1 + -1p) Combine like terms: 2p + -4p = -2p 4 + -2p = 4 + -1(2)(1 + -1p) Multiply -1 * 2 4 + -2p = 4 + -2(1 + -1p) 4 + -2p = 4 + (1 * -2 + -1p * -2) 4 + -2p = 4 + (-2 + 2p) Combine like terms: 4 + -2 = 2 4 + -2p = 2 + 2p Solving 4 + -2p = 2 + 2p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-2p' to each side of the equation. 4 + -2p + -2p = 2 + 2p + -2p Combine like terms: -2p + -2p = -4p 4 + -4p = 2 + 2p + -2p Combine like terms: 2p + -2p = 0 4 + -4p = 2 + 0 4 + -4p = 2 Add '-4' to each side of the equation. 4 + -4 + -4p = 2 + -4 Combine like terms: 4 + -4 = 0 0 + -4p = 2 + -4 -4p = 2 + -4 Combine like terms: 2 + -4 = -2 -4p = -2 Divide each side by '-4'. p = 0.5 Simplifying p = 0.5
| 9.5=92.4 | | 0=2xc(x)-x | | 82-115=-8(-4y)-17(2y)+y | | 8x-.2=9.8 | | 80x+40=84x | | Y-8=4(x-5) | | -4i= | | 5x+(-4y)+(-15x)+6y= | | 64+a^6= | | 2y+4x=-1 | | -(2x-5y)= | | 9(2x+10)-7x*4= | | 7(5a+3b)+7(2a+4b)= | | x-18=-1-10 | | -5(4p+3)-31=2(5p+7) | | 8a^3-1= | | 3(3x-9)-2=3(x-5)+16 | | h/15=-7 | | (4x+5)6= | | 4-8n+3n=8-99 | | 9659-268(6)=8262 | | -49+7y+6=2(5y-4)-8 | | 3.2x=-9.6 | | 9[6-(-9x-4)]=729x+378 | | -2x-y=-16 | | -2(x+4)=2x+4 | | 2(-x+3x)3(-x)+7=(-x)+(-3) | | x=x+6.48 | | (2x^3+7)(2x^3+6)= | | 9(c-5)+8=5+c-42 | | m-7m+9m+7= | | 4x-3=-2x+7+8x |